Parametric Analysis of a Mechanical Draft Cooling Tower using Two Mathematical Models (2021)
In the present work, a Matlab® computer code for cooling tower simulation was developed to perform a parametric analysis that determines the effect of the column cross-sectional area on multiple operating variables such as air humidity, air and water outlet temperature, among others. The computer code uses the Merkel's model and the CDAWC (Continuous Differential Air-Water Contactor) model for later comparison. It was observed a decrease in the outlet water temperature by approximately 14% when the tower's cross-sectional area increased from 1 to 2 m2. It increases the air outlet temperature by about 17% due to increased air-water contact. A negative convective heat transfer in the air was obtained in the cooling tower´s bottom due to the large amount of energy required for the heat transfer by vaporization, which was much larger than the convective heat. The evaporative heat transfer is over 80% of the total heat transferred.